2018
DOI: 10.1080/2162402x.2017.1419115
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived thymic stromal lymphopoietin enhances lung metastasis through an alveolar macrophage-dependent mechanism

Abstract: It is well-recognized that macrophages, which arise from circulating precursors, enhance tumor progression in patients and animal models. However, less is known regarding the role of tissue-resident macrophages in metastasis. Moreover, the identification of tumor factors which influence macrophage function in the metastatic niche remains incomplete. Here, we investigated one such cytokine known as thymic stromal lymphopoietin (TSLP). Our rationale to focus on TSLP was based on two non-overlapping findings; fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Experiments in TSLP KO mice then showed that TSLP signaling was required for metastatic disease progression to the lung. In another study (33), tumor cell-derived TSLP induced invasive and angiogenic gene expression profiles in alveolar macrophages. Depletion of alveolar macrophages but not macrophages from the circulation impacted lung lesion growth.…”
Section: Breast Cancermentioning
confidence: 92%
“…Experiments in TSLP KO mice then showed that TSLP signaling was required for metastatic disease progression to the lung. In another study (33), tumor cell-derived TSLP induced invasive and angiogenic gene expression profiles in alveolar macrophages. Depletion of alveolar macrophages but not macrophages from the circulation impacted lung lesion growth.…”
Section: Breast Cancermentioning
confidence: 92%
“…Thymic stromal lymphopoietin (TSLP) was abundantly expressed by several mouse and human breast cancer cell lines. Tumor cell-derived TSLP induced AMs to express VEGF-A, platelet-derived growth factor-A, and MMP-9 thereby promoting lung metastasis [61]. In this model, intratracheal CLL injection reduced AMs but not IMs, together with reduced metastatic burden.…”
Section: Monocytes and Macrophages In The Lung With Metastatic Tummentioning
confidence: 99%
“…Although TSLP is expressed by epithelial cells, keratinocytes, mast cells, and basophils in response to a range of stimuli, including cancer cell-derived IL1a, IL1b, TNFa, IL13, and TGFb (18), progression and metastasis of some cancers also require TSLP production from cancer cells themselves. TSLP's purpose is to induce production of survival factors (19) or to activate invasive and angiogenic properties of alveolar macrophages (20). We reported that 4T1 cancer cell-produced TSLP induces Th2-skewed and CCL17-elevated lung environment (16) to enable coinfiltration of CCR4 þ cancer cells and their protector CCR4 þ Tregs in the lungs (6,16,21).…”
Section: Introductionmentioning
confidence: 99%